Effects of fermentation time and pH on soursop (Annona muricata) vinegar production towards its chemical compositions - Chin, Wai Ho; Azwan Mat Lazim,; Shazrul Fazry,; Umi Kalsum Hj Hussain Zaki,; Lim, Seng Joe (Penerbit Universiti Kebangsaan Malaysia, 2017)
Vinegar is a liquid product that undergoes both alcoholic and acetous fermentation of sugar (carbohydrate) sources. Soursop (Annona muricata) is easily available in Malaysia throughout the year. However, it is also highly perishable and has a short shelf-life. Therefore, in this research, soursop was used in the production of vinegar, to increase its utilisation and reduce wastage. The objectives of this research were to determine the effects of fermentation time and pH on soursop vinegar using a 3 × 5 factorial design and to determine its chemical compositions. It was found that pH and fermentation time showed significant (p<0.05) effects on the reduction of sugar content and the production of acetic acid, while only fermentation time showed a significant effect on the production of ethanol. The interaction between factors did not exhibit any statistical significance (p>0.05). It was evident that the sugar concentration reduces over time and it was inversely proportional to the ethanol and acetic acid concentrations, due to the conversion of sugar to ethanol and subsequently acetic acid. It was found that higher pH (pH5.5) gave significantly (p<0.05) higher acetic acid production in the vinegar, while pH has no significant (p>0.05) effect on ethanol production. There were no significant differences (p>0.05) in vitamin C content in all vinegar samples. Thus, it can be established that at fermentation time of 120 h and pH5.5, more sugar was used and more ethanol and acetic acid were produced.